High-Resolution Morphologic and Ultrashort Time-to-Echo Quantitative Magnetic Resonance Imaging of the Temporomandibular Joint - Bae, Won C (Skeletal Radiol, 2015)
OBJECTIVE: To implement high-resolution morphologic and quantitative magnetic resonance imaging (MRI) of the temporomandibular joint (TMJ) using ultrashort time-to-echo (UTE) techniques in cadavers and volunteers. METHODS: This study was approved by the institutional review board. TMJs of cadavers and volunteers were imaged on a 3T-MR system. High-resolution morphologic and quantitative sequences using conventional and UTE techniques were performed in cadaveric TMJs. Morphologic and UTE quantitative sequences were performed in asymptomatic and symptomatic volunteers. RESULTS: Morphologic evaluation demonstrated the TMJ structures in open and closed-mouth position. UTE techniques facilitated the visualization of the disc and fibrocartilage. Quantitative UTE MRI was successfully performed ex-vivo and in-vivo reflecting the degree of degeneration. There was a difference in the mean UTE T2* values between asymptomatic and symptomatic volunteers. CONCLUSIONS: MRI evaluation of the TMJ using UTE techniques allows characterization of the internal structure and quantification of the MR properties of the disc. Quantitative UTE MRI can be performed in-vivo with short scan times.